Hemolytical Profile Of Streptococcus Spfrom Nasal Swab Isolation At Traditional Farm In Bongkasa Village, Abiansemal Subdistrict, Badung Regency, Bali. - Yanti, Ni Luh Made Siska; Suardana, I Wayan; Suarjana, I Gusti Ketut; Suarjana, I Gusti Ketut (Journal of Veterinary and Animal Sciences, 2019)
Streptococcus sp is Gram positive cocci and aligned like chain. This bacteria can be found normally in upper respiratory tract. Streptococcus sp can be divided into two groups; able to hemolize blood and unable. B-hemolytic  Streptococcus tend to be more pathogen than the others. Therefore this research about Streptococcus sp’s hemolysis profile is very important. The samples of this research is an isolated swine nasal swab from a traditional pig farm in Bongkasa Village. 20 samples were used in this research. Samples were grown in Blood Agar media to find out the capability of bacteria for hemolizing blood. Catalase test used for differentiating Streptococcus sp and Staphylococcus sp, followed by oxydase test after. Result of the research shows positive samples of Streptococcus sp divided by hemolysis profile is 11 isolates whereas 36,4% isolates were Alfa hemolysis, 54,6% were B hemolysis, and 9% isolates were Gamma hemolysis.